The Role of Human Resource Management in Enhancing Positive Psychological Capital among Employees in the Government Sector in Saudi Arabia in light of Vision 2030, in Riyadh - Al-Qahtani, Sarah Hamoud AlHamali; Al-Dosari, Sarah Mubarak; Al-Tawili, Amal Abbas (Journal of Economic, Administrative and Legal Sciences, 2024)
Human capital is considered as a vital resource in various sectors, including the government sector. It plays a significant role in the achievements and aspirations of these sectors. The government sector has witnessed great attention in the development and improvement of human capital, given its importance, including the psychological aspect.The Saudi Arabia Vision 2030 aims to create a thriving society and a leading economy. Therefore, it seeks to enhance the psychological capital of government sector employees for its crucial role in achieving this vision. This study aims to identify the role of human resource management in enhancing the psychological capital of employees in the government sector in Saudi Arabia in line with Vision 2030.The researchers conducted an electronic survey from November 2023 to December 2023 by distributing questionnaires to a sample of human resource employees, managers, and workers in the government sector. The data was analyzed to obtain clear results according to the timeline. The primary data includes information about the study sample according to the independent variables of the study, such as job position, gender, and years of experience.The study tool consists of 21 statements distributed across four axes:the managerial role of human resource management in enhancing positive psychological capital,   implementing Vision 2030 in human resource management, the managerial role of top leadership in enhancing employees' psychological capital, consisting of six statements, and the challenges and difficulties facing the enhancement of employees' psychological capital. A five-point Likert scale was used to answer the statements (strongly agree - agree - neutral - disagree - strongly disagree).
Keywords: The government sector; psychological capital; human resource management; Saudi Arabia; Vision 2030